Immunization status of children with cerebral palsy: A cross-sectional hospital-based study in Vietnam - Thi Hong Hanh Khuc; Tasneem Karim; Minh Chau Cao; Thi Van Anh Nguyen; Thi Huong Giang Nguyen; Quang Dung Trinh; Rachael Dossetor; Van Bang Nguyen; Nadia Badawi; Lal Rawal; Gulam Khandaker; Elizabeth Jane Elliott (PLoS ONE, 2025)
Aim To describe the immunization status of children with CP in Vietnam and identify factors associated with vaccine non-uptake in this group. Methods We conducted an active prospective case ascertainment of children with cerebral palsy (CP) attending the National Children’s Hospital in Hanoi between June to November 2017, following the model proposed by the Paediatric Active Enhanced Disease Surveillance system in Australia. All children were assessed by trained paediatricians at the hospital and their immunization history was recorded. Results Data were collected from 765 children with CP (median age = 1.7 years, IQR = 2.7 years). Of these children, 82.7% were fully immunized for their age (compared to 96.4% of the general child population) according to the Vietnamese Expanded Programme on Immunization (EPI) schedule. A BCG vaccination scar was present in 94.0% of children with CP, and 95.9% of eligible children had received the measles-rubella vaccine as part of the national campaign (compared with 96.0% and 98.2% of the general population respectively). Incomplete vaccination according to the EPI was associated with younger age, living in an earth/sand house, homebirth, low-level maternal education, being diagnosed with CP before the age of three, having bilateral CP, having associated impairments (i.e., epilepsy, intellectual, visual, speech), being at level IV-V on the Gross Motor Function Classification System, and being undernutrition. Conclusion This is the first study to document the immunization status of children with CP in Vietnam. A large proportion had not received the measles-rubella vaccine and 17.3% were not fully immunized. To increase vaccination coverage, interventions and strategies are required to ensure that all children with CP have equitable access to early diagnosis, immunization, health education programs, outreach programs, and frequent follow-up. Early diagnosis and focused intervention in early life could further improve vaccination coverage in children with CP.